International economics,theory & policy - Krugman, Paul R.,Obstfeld, Maurice,Melitz, Marc J.
International economics : theory & policy / Paul R. Krugman, Maurice Obstfeld, Marc J. Melitz .- Harlow : Pearson Education , 2011 .- 731 p. ; 27 cm .- 9780273754091